Regenerative viticulture and climate change resilience - Flora O'Brien; Alistair Nesbitt; Rebecca Sykes; Belinda Kemp (OENO One)
Regenerative viticulture (RV) draws on disciplines and concepts such as ecology, agroecology, functional biodiversity, ecosystem services and permaculture, integrated into vineyard management to enhance both production and environmental outcomes. Its core aims are to regenerate vineyard soils and biodiversity, support vine health, enhance vineyard ecological conditions and resilience, and mitigate climate change. The purpose of this review was to evaluate the literature concerning individual, yet often interconnected components of, and approaches to RV, including soil management, cover crops, weeds, pests and diseases, and livestock integration, to establish current knowledge and inform future research opportunities. Where sufficient evidence was available, we also address the impact of RV related practices on vineyard performance, and grape and wine quality characteristics. The review found literature and science supporting viticulture’s potential for: soil and biodiversity regeneration, carbon sequestration, land cooling, ecological enhancements, and soil water holding capacity improvements. There is less consensus regarding the impact of RV approaches on grape yield, wine quality and greenhouse gas (GHG) emissions, as well as a lack of vineyard-based evidence demonstrating the efficacy of biostimulants and Biological Control Agents (BCAs). Research covering a range of regional or context specific environments regarding regenerative approaches or practices are limited, particularly when seeking to address opportunities for, and impacts of whole vineyard systems change–this is a complex area that has not yet been fully addressed. Findings illustrate the emerging status of RV as a researched and/or applied concept, and this review supports those establishing RV systems and contributes to evidence-based RV approaches. It also supports policymakers by highlighting aspects of RV that contribute to the provision and protection of ecosystem services, climate change mitigation and vineyard resilience, fostering opportunities in viticulture.